2018
DOI: 10.2224/sbp.6564
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of personality factors in breast cancer screening behavior

Abstract: Although the efficacy of breast cancer screening in Iran has improved, the participation of women is not yet at a satisfactory level. Some personality factors can prevent women from attending breast cancer screening and most tumors are still diagnosed at an advanced stage. We conducted a descriptive exploration study in which we recruited healthcare providers, policymakers, and clients in Iran as participants. We used conventional content analysis with an inductive approach and gathered data from 2 discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to the results noted by Ghahramanian et al, (2016) 10.8% of women referred to health centers of Tabriz city in Iran, believed in fatalism. Moreover, the findings of some qualitative studies indicated that participating women mainly mentioned fatalism as a feeling of lack of control to prevent breast cancer [17, 18]. In this regard, Charkazi et al, (2013) showed that Iranian Turkmen women had high fatalism belief.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results noted by Ghahramanian et al, (2016) 10.8% of women referred to health centers of Tabriz city in Iran, believed in fatalism. Moreover, the findings of some qualitative studies indicated that participating women mainly mentioned fatalism as a feeling of lack of control to prevent breast cancer [17, 18]. In this regard, Charkazi et al, (2013) showed that Iranian Turkmen women had high fatalism belief.…”
Section: Introductionmentioning
confidence: 99%
“…These were based on a woman’s role in the household (Theme 1.1.1); women were expected to prioritise looking after their family’s needs and managing domestic responsibilities due to their position as wives and mothers ( Macdonald et al, 2015 , Urrutia et al, 2017 , Yang et al, 2019 , Trigoni et al, 2008 , Nyblade et al, 2017 , Thomas et al, 2011 , Safizadeh et al, 2018 , Shirzadi et al, 2020 , Rasul et al, 2015 , Baron-Epel et al, 2004 , Azaiza and Cohen, 2008 , Ngugi et al, 2012 , Wong et al, 2008 , Markovic et al, 2005 , Khan and Woolhead, 2015 , Daley et al, 2012 , Filippi et al, 2013 , Tessaro et al, 1994 , Nekhlyudov et al, 2003 , Nolan et al, 2014 , Nonzee et al, 2015 ). Women in the included studies also expressed that there were sociocultural expectations on female behaviour (Theme 1.1.2); they were expected to care for others’ health above their own ( Trigoni et al, 2008 , Wong et al, 2008 , Filippi et al, 2013 , Tessaro et al, 1994 , Thomas et al, 2011 , Safizadeh et al, 2018 , Shirzadi et al, 2020 , Rasul et al, 2015 , Nolan et al, 2014 , Nonzee et al, 2015 , McMichael et al, 2000 , Manderson and Hoban, 2006 , Dey et al, 2016 , Savabi-Esfahani et al, 2018 , Khazaee-pool et al, 2014 , Khazir et al, 2019 ), and were expected to have a sense of modesty that was incompatible with the bodily exposure required during breast or cervical screening ( Macdonald et al, 2015 , Azaiza and Cohen, 2008 , Isa Modibbo et al, 2016 , Püschel et al, 2010 , Ndejjo et al, 2017 ). However, women in several studies also mentioned that there was a motivation to engage in cancer screening in order to stay healthy for the sake of their family.…”
Section: Resultsmentioning
confidence: 99%
“…fewer opportunities to learn and/or acquire information) context ( Macdonald et al, 2015 , Yang et al, 2019 , Ngugi et al, 2012 , Markovic et al, 2005 , Daley et al, 2012 , Filippi et al, 2013 , Nolan et al, 2014 , Ndejjo et al, 2017 , Kahn et al, 2006 , Binka et al, 2019 , Onyenwenyi and Mchunu, 2018 , Brandt et al, 2019 , Teng et al, 2014 , Oscarsson et al, 2008 ). Women were also more likely to need financial support (Theme 3.2) and be financially dependent on spouses or their families ( Shirzadi et al, 2020 , Ngugi et al, 2012 , Filippi et al, 2013 , Tessaro et al, 1994 , Ndejjo et al, 2017 , Binka et al, 2019 , Shaw et al, 2018 , Mutyaba et al, 2007 , Pelcastre-Villafuerte et al, 2007 , Darj et al, 2019 , Urrutia et al, 2017 , Yang et al, 2019 , Trigoni et al, 2008 , Dey et al, 2016 , Savabi-Esfahani et al, 2018 , Khazaee-pool et al, 2014 , Khazir et al, 2019 , Granado et al, 2014 , Bahmani et al, 2016 , Malhotra et al, 2016 , Gu et al, 2017 , Andrasik et al, 2008 , Ersin and Bahar, 2011 , Lovell et al, 2007 , Holroyd et al, 2004 ). Lastly, women in several studies highlighted practical barriers (Theme 3.3) that prevented them from attending breast and cervical screening programmes, even if there was the intention to do so.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in educating women, they should be sensitized about the risk of breast cancer and the norms of that society about self-care behaviors should be examined [17]. In Iranian society, fear of cancer diagnosis [18]., lack of trust in health team members, lack of independence in decision-making among women, fatefulness, lack of women's empowerment [19]., and personality traits (not paying attention to one's health and prioritizing family, as well as emotional responses such as the con icting effects of fear and shame) are the most important obstacles to women's participation in self-care programs [20,21]. In order to remove these obstacles, the design of prevention programs according to the economic, social and cultural conditions of the Iranian society seems to be necessary.…”
Section: Discussionmentioning
confidence: 99%